2011
DOI: 10.3390/ijms12106385
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tamarindus indica Extracts for Antibacterial Activity

Abstract: Ethanolic and aqueous (hot and cold) extracts of the fruit pulp, stem bark and leaves of Tamarindus indica were evaluated for antibacterial activity, in vitro, against 13 Gram negative and 5 Gram positive bacterial strains using agar well diffusion and macro broth dilution techniques, simultaneously. The fruit pulp extracts exhibited a wide spectrum of activity; the cold water extract against 95.5% of the test bacterial strains; and the hot water and ethanolic extracts against 90.9% and 86.4%, respectively. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 8 publications
6
25
1
8
Order By: Relevance
“…The ethanolic extract contains alkaloids and coumarins while aqueous extract does not contain alkaloids and coumarins as in line with the reported elsewhere [44] but differs in the detection of tannins and flavonoids (in aqueous leaves extract) which was found to be absent in all the extracts during the experiment. It is in agreement with Nwodo et al [45] but differs in glycosides and flavonoids which were found to be absent in aqueous leaves extract. Furthermore, Abukakar, et al [36] reported the presence of alkaloids in the aqueous leaves extract, but in contradiction, it was absent in this study.…”
Section: Phytochemical Screening Of T Indica Leaves Extractssupporting
confidence: 92%
“…The ethanolic extract contains alkaloids and coumarins while aqueous extract does not contain alkaloids and coumarins as in line with the reported elsewhere [44] but differs in the detection of tannins and flavonoids (in aqueous leaves extract) which was found to be absent in all the extracts during the experiment. It is in agreement with Nwodo et al [45] but differs in glycosides and flavonoids which were found to be absent in aqueous leaves extract. Furthermore, Abukakar, et al [36] reported the presence of alkaloids in the aqueous leaves extract, but in contradiction, it was absent in this study.…”
Section: Phytochemical Screening Of T Indica Leaves Extractssupporting
confidence: 92%
“…The seed polysaccharide of T. indica appears to be a potential promising candidate, as a vehicle for the topical treatment of bacterial keratitis (Ghelardi, ). The ethanolic extract that was hot and aqueous extract that was cold of fruit pulp, stem bark, and leaves of tamarind are of efficient use against the species of B. subtilis ATCC, P. aeruginosa , E. coli , and B. subtilis (Nwodo, Obiiyeke, Chigor, & Okoh, ).…”
Section: Health Perspectives Of Tamarindmentioning
confidence: 99%
“…The ethanolic extract that was hot and aqueous extract that was cold of fruit pulp, stem bark, and leaves of tamarind are of efficient use against the species of B. subtilis ATCC, P. aeruginosa, E. coli, and B. subtilis(Nwodo, Obiiyeke, Chigor, & Okoh, 2011).The alcoholic extract of T. indica seeds (200 µg/ml) exhibited the antibacterial activity against P. aerugnosia, E. coli, S. dysentery, S. typhi, Enteriococcus sp., S. auerus, and B. subtilus. The species S. typhi and E. coli were more susceptible to the seed extract when compared to other bacterial isolates with the inhibition zone up to 35 mm.…”
mentioning
confidence: 99%
“…Situations where purification has led to loss of activity have been reported. Even not in all cases, fractionation of Tamarindus indica led to loss of activity to E. coli [23]. In the study of antifungal activity, demonstrated the lost activity in some medicinal plants after the separation of the plant extracts into precipitant and supernatant [24].…”
Section: Ic50 Cc50 and Si Of P Indicusmentioning
confidence: 99%